El maestro como agente de cambio contra el racismo: Del preguntar y preguntarse en el dispositivo pedagógico didáctico - Soler Castillo, Sandra (Colombian Applied Linguistics Journal, 2025)
This reflective pedagogical reflective article argues for incorporating questioning and self-questioning as fundamental epistemological and ontological dimensions within the pedagogical-didactic framework. Questioning helps to clarify the object of pedagogical-didactic action, while self-questioning examines how teachers positions themselves in relation to this object. The article suggests principles for pedagogical practice aimed at enriching teachers' pedagogical actions and enabling them to articulate what they know and experience in their work. From a language ontology that emphasizes the discursive nature of being and its capacity to explain itself and the world, five domains of reflection are proposed: experiential, discursive, performative, moral, and emotional. For each domain, links to racism are identified, and a set of guiding questions is suggested as activation principles for an anti-racist pedagogical-didactic framework. The article concludes that the value of questioning, understood in its ontological and epistemological dimensions, fosters greater critical and creative awareness in teachers regarding their pedagogical practice, equipping them to confront racism as a persistent and resistant force in classrooms and educational institutions.